Up island : a novel - Siddons, Anne Rivers (New York, NY : HarperCollinsPublishers, 1997)
When her perfect life begins to crumble, Molly Bell Redwine--dutiful daughter, perfect wife, nurturing mother, and family protector--journeys to Martha's Vineyard in search of refuge, the meaning of life, and her own place in the world
Keywords: Women -- Massachusetts -- Martha's Vineyard -- Fiction; Women -- Identity -- Fiction; Martha's Vineyard (Mass.) -- Fiction; Domestic fiction